RFID based systematic student's attendance management system - Hanisah, Hamid (2010)
Most educational institutions’ administrators are concerned about student irregular attendance. Truancies can affect student overall academic performance. The conventional method of taking attendance by calling names or signing on paper is very time consuming and insecure, hence inefficient. Therefore, computer-based student attendance management system is required to assist the faculty and the lecturer for this time-consuming process. For this project, RFID based systematic student’s attendance management system can provide much convenient method to take attendance, but some prerequisites has to be done before start using the program. Although the use of RFID systems in educational institutions is not new, it is intended to show how the use of it came to solve daily problems in our university. Assisted by the System Development Life Cycle (SDLC) methodology, the system has been built using the web-based applications such as JSP, MySQL and Apache to cater the recording and reporting of the students’ attendances. NetBeans IDE 6.1 is used for developing the overall system, MySQL as the database and Java act as the scripting programming language. RFID Based Systematic Student’s Attendance Management System was built using open source software and it will reduce the cost of development process. The system can be easily accessed by the lecturers via the web and most importantly, the reports can be generated in real-time processing, thus, providing valuable information about the students’ commitments in attending the classes.